Important Role of a Putative Lytic Transglycosylase Cj0843c in β-Lactam Resistance in Campylobacter jejuni - Zeng, Ximin; Gillespie, Barbara; Lin, Jun (Frontiers in Microbiology, 2015)
Beta-lactam antibiotics are an important class of antibiotics for treating bacterial infections. Despite prevalent β-lactam resistance in Campylobacter jejuni, the leading bacterial cause of human diarrhea in developed countries, molecular mechanism of β-lactam resistance in C. jejuni is still largely unknown. In this study, C. jejuni 81-176 was used for random transposon mutagenesis. Screening of a 2,800-mutant library identified 22 mutants with increased susceptibility to ampicillin. Of these mutants, two mutants contains mutations in Cj0843c (a putative lytic transglycosylase gene) and in its upstream gene Cj0844c, respectively. Molecular manipulation in different strains demonstrated that Cj0843c contributes to both intrinsic and acquired β-lactam resistance in C. jejuni. Consistent with this finding, inactivation of Cj0843c also dramatically reduced β-lactamase activity. Genomic examination and PCR analysis showed Cj0843c is widely distributed in C. jejuni. The Cj0843 was localized in the periplasm as demonstrated by immunoblotting using specific antibodies. Turbidimetric assay further demonstrated the capability of the purified Cj0843c to hydrolyze cell walls. Inactivation of Cj0843c also significantly reduced C. jejuni colonization in the intestine. Together, this study identifies a mechanism of β-lactam resistance in C. jejuni and provides insights into the role of cell wall metabolism in regulating β-lactamase activity.